An enhancement of handoff latency reduction mechanism for mobile internet protocol version 6 (MIPV6) - Masud, Mosharrof Hussain (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Mobile Internet Protocol Version 6 (MIPv6) is envisioned for next generation networks to achieve seamless communication as it has more suitable features than the existing version. However, MIPv6 is not yet deployed for some limitations like handoff latency and security that degrades Quality of Service (QoS). Therefore, two different handoff latency solutions are proposed for MIPv6 networks. Handoff latency solution 1 consists of two parts related to Layer 2 (L2) and Layer 3 (L3), using fuzzy logic to reduce latency of L2 scanning phase, and a Parallel Duplicate Address Detection (PDAD) to reduce the address configuration time in L3. Solution 2 is incorporated with IEEE 802.21 ~MIH (Media Independent Handover) assisted with MIPv6 which configures the alternative interface while the mobile node (MN) is using an active interface without disturbing the current session. These two mechanisms are evaluated using performance metrics of handoff latency and packet Joss. The performance of the mechanisms is evaluated using OMNeT ++ and MA TLAB. The overall hand off latency is reduced from standard I 300 ms to 500 ms using solution 1, a 60% reduction, with packet loss reduction of 70%. The second solution reduces both handofflatency and packet loss by 75%.